ANALISIS PENGGUNAAN TEKS MULTIMODAL UNTUK MENINGKATKAN KEMAMPUAN LITERASI DI SEKOLAH DASAR - Auliyana Rahmah Harahap; Siti Putri Ardiyanti Pasaribu; Vidiani Sembiring; Mara Untung Ritonga; Abdurahman Adisaputra (SOKO GURU: Jurnal Ilmu Pendidikan, 2025)
Literacy skills are a fundamental element in primary education that influence students' success in various fields. However, the results of the PISA survey show that the literacy levels of Indonesian students are still unsatisfactory. One innovative approach that can improve students' literacy skills is the use of multimodal texts. Multimodal texts integrate various modes of communication such as written text, images, audio, and video to convey information, which is believed to enhance student engagement and understanding in the learning process. Several studies indicate that the application of multimodal texts can improve science literacy, reading comprehension, and writing skills among primary school students. This study employs the Systematic Literature Review (SLR) method to identify, evaluate, and synthesize various studies related to the use of multimodal texts in literacy learning at the primary school level. The analysis results show that multimodal texts are effective in enhancing students' literacy skills, particularly in reading and writing. Therefore, the integration of multimodal texts into the primary school curriculum is highly recommended to improve the quality of learning and student learning outcomes